Dystrophic calcinosis cutis in a patient with cutaneous sarcoidosis in remission. Issue 1 (29th September 2022) - Yoshikawa, Miyuki; Akasaka, Eijiro; Nakano, Hajime; Sawamura, Daisuke
Abstract: A 65‐year‐old Japanese woman was referred to our department because of a 5‐month history of asymptomatic papules on the face. She was diagnosed with cutaneous sarcoidosis on the face 20 years ago. All of the lesions had completely disappeared with oral corticosteroids. Twenty years after the diagnosis of sarcoidosis, small papules developed in areas where the cutaneous sarcoidosis had been located. Physical examination revealed four yellow‐white papules on the face. Dermoscopy revealed a homogenous, round, and yellow‐white lesion. Serum levels of calcium and phosphorus were normal. Histopathology demonstrated calcium deposits in the dermis surrounded by inflammatory infiltrates without sarcoid granulomas. We made a diagnosis of calcinosis cutis. Basal cell carcinoma with calcinosis cutis, milia‐like calcinosis cutis, and subcutaneous calcified nodule should be differentiated. Calcinosis cutis can be classified into four subtypes based on pathogenesis: dystrophic, metastatic, idiopathic, and iatrogenic. Dystrophic calcinosis cutis is caused by local tissue damage or abnormalities. Whereas, metastatic calcinosis cutis is often associated with hypercalcaemia, hyperphosphatemia, or hyperparathyroidism. There are reported cases of metastatic calcinosis cutis associated with sarcoidosis because patients with sarcoidosis often present with hypercalcaemia. However, dystrophic calcinosis cutis associated with sarcoidosis has been rarely reported. In the present case, systemic treatment for sarcoidosis may have degraded sarcoid granulomas and yielded necrotic tissue and dermal fibrosis, which might have induced ectopic calcification. Thus, we thought the present case consisted of dystrophic calcinosis cutis that developed in areas with cutaneous sarcoidosis in remission. Abstract : We present a case of dystrophic calcinosis cutis on the face. They developed in areas with cutaneous sarcoidosis in remission.